ANALISA PERSAINGAN BANK UMUM DENGAN BANK SYARIAH DITINJAU DARI TINGKAT SUKU BUNGA: (Berdasar Suku Bunga Bank Indonesia dan Bagi Hasil Mandiri Syariah Periode Tahun 2007-2011) - Posma Sariguna Johnson Kennedy; Hardi Surya Surya (Fakultas Ekonomi Universitas Kristen Indonesia, 2015)
This study aimed to see if the selection by the consumer bank in placing deposits due to the rate of return / interest, or because of the type of the bank. The approach used in this study is a quantitative approach, with multiple linear regression analysis technique. The type of data in this research is secondary data, in the form of time series data in the period of 2007-2011 on a monthly basis, which consist of interest rate of Bank Indonesia, the sharia deposit rate for one month in Mandiri Syariah, and the amount of funds on bank deposits in Mandiri Syariah. The results showed that the depositors have not seen the kind of bank where they place their funds, but still see the risk and return, which still compare the rate of profit from the interest rate offered by commercial banks that are shown on the rise and fall of interest rates of Bank Indonesia.Keywords: financial management, sharia banks, deposits.